Introgression of Powdery Mildew Resistance Gene Pm56 on Rye Chromosome Arm 6RS Into Wheat - Hao, Ming; Liu, Meng; Luo, Jiangtao; Fan, Chaolan; Yi, Yingjin; Zhang, Lianquan; Yuan, Zhongwei; Ning, Shunzong; Zheng, Youliang; Liu, Dengcai (Frontiers in Plant Science, 2018)
Powdery mildew, caused by the fungus Blumeria graminis f. sp. tritici, represents a yield constraint in many parts of the world. Here, the introduction of a resistance gene carried by the cereal rye cv. Qinling chromosome 6R was transferred into wheat in the form of spontaneous balanced translocation induced in plants doubly monosomic for chromosomes 6R and 6A. The translocation, along with other structural variants, was detected using in situ hybridization and genetic markers. The differential disease response of plants harboring various fragments of 6R indicated that a powdery mildew resistance gene(s) was present on both arms of rye chromosome 6R. Based on karyotying, the short arm gene, designated Pm56, was mapped to the subtelomere region of the arm. The Robertsonian translocation 6AL•6RS can be exploited by wheat breeders as a novel resistance resource.